Nautical Patrol and Illegal Fishing Practices - Stephen Kastoryano; Ben Vollaard (Institute of Labor Economics (IZA), 2022)
We uncover a hidden illegal fishing practice: the use of fishing nets with illegally small mesh size. The small mesh prevents nearly all fish of saleable size from escaping the net, but also traps a large number of fish which are too small to be sold on the market and are therefore discarded at sea. Our approach relies on readily available data on reported fish landings rather than on data from inspections, which are rare, and which tend to be anticipated by fishermen. We focus on bottom trawling, the world's most widely used fishing method. We exploit the fact that using illegally small mesh size strongly increases the share of small fish in the catch. Using quasi-random variation in nautical patrol as a source of variation in the incentive to comply, we show that in weeks without patrol the share of small fish in the landed catch is systematically larger than in adjacent weeks with patrol. Our results are in line with widespread use of illegally small mesh.
Keywords: D22; K42; Q22; 330; enforcement; regulation; environmental economics; fisheries